'Urf Marriage of Gampong Padang Residents in Setia Bakti District, Aceh Jaya Regency: 'Urf Pernikahan Warga Gampong Padang di Kecamatan Setia Bakti Kabupaten Aceh Jaya - Rahmayani, Rahmayani; karim, Ihdi; Eriyanti, Nahara (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
There are often various customs of marriage customs in society. From these marriage habits, some are not contrary to Sharia but there are also the opposite. For this the customs/customs of marriage need to be traced using the review of 'urf, so that it is thus identified whether it belongs to 'urf shahih or 'urf fasid. From that, this study formulated two problems, including how the marriage habits carried out by a small number of Gampong Padang residents and what 'urf reviews these marriage habits are. To answer these two formulations, the author uses a library research method with several approaches, namely the case approach, legislation, and the 'urf theory approach. The result obtained from this study is that there is a small percentage of Gampong Padang residents who hand over the fate of their marriage to someone who is held under the name waled / walidi. After collecting several waled people then determined a mate against them. After the arranged marriage proceeds to the stage around sawa mountain, to the tomb of ureung malem for the ritual summoning of ancestral spirits and sirri marriage. Based on these data, researchers categorize the marriage habit into two forms of 'urf, namely shahih and fasid. What is included in the urf shahih is the arranged marriage and marriage of sirri, the arranged marriage is done voluntarily and so is the sirri marriage carried out according to the marriage. Meanwhile, what is included in the 'urf fasid is to surround the sawa mountain and to the tomb of the mountain malem for ancestral spirit summoning rituals, because it contains shirk and adultery. It should not be a custom that is fasid because a concept of custom can be done if it does not conflict with the syara'.